Kombinasi Teknik Contrast Bath Dan Foot Massage Dalam Menurunkan Edema Kaki Pada Ibu Hamil Dengan Preeklamsia Berat - Pasambo, Yourisna; Radjak, Desy Fransiska; Tamunu, Esther; Tuegeh, Johana; Karundeng, Yanni (POLTEKKES KEMENKES MANADO, 2024)
Background: Preeclampsia is a set of symptoms experienced by pregnant women, laboring women and women in the postpartum period that usually appear at 20 weeks of gestation until the end of the first week of labor. Leg edema is a common problem in pregnant women with preeclampsia. Leg edema makes pregnant women feel cramps at night, feel uncomfortable and heavy in the swelling area. The management of foot massage and warm water soak is effective in reducing leg edema in third trimester pregnant women. Contrast bath is one of the foot soaking techniques that works to reduce edema by lowering intra-venous hydrostatic pressure which has an impact on the seeping of plasma fluid in the interstitium back into the veins. Objective : of this case study is to apply evidenced based nursing action contrast bath with foot massage to reduce leg edema in pregnant women with severe preeclampsia. The writing. Methods : is descriptive qualitative using a case study approach. Samples were selected using purposive sampling technique and obtained a sample of four pregnant women with severe preeclampsia. Results: the four pregnant women experienced a decrease in edema degree of 1 degree each after being given contrast bath and foot massage interventions for three days. Conclusion: the combination of contrast bath and foot massage techniques is effective in reducing leg edema